Effect of Exercises Using Training Aids on the Development of Explosive Strength and Accuracy of Some Throwing Skills of Boccia players with Sever disabled Category (Bc1) - Mohammed, Ahmed; Rasheed, Abedullah (Journal of Physical Education, 2018)
Effect of Exercises Using Training Aids on the Development of Explosive Strength and Accuracy of Some Throwing Skills of Boccia players with Sever disabled Category (Bc1)The research indicates the importance of the players’ explosive power Boccia and how it affects the skill performance of the players. Explosive strength is considered one of the most important physical abilities. The game is based mainly on accuracy although some player suffer from reflexive movements that causes difficulty in controlling the ball, which in turn affect the performance of skills, through the presence of the researcher as a referee approved by the Federation of Boccia and the experience of the supervisor in the sport of disabled and after consulting with the coach of the team Boccia We noticed that there is weakness in physical abilities. The researcher used the experimental method. The subject were (5) selected in a deliberate manner and they are players of the national team for applicants with severe disabilities (cerebral palsy) participants in the 2017 Iraq, and the research community were (10) as the proportion of the sample (50%) of the research community. The researchers concluded that the physical exercises developed explosive strength and accuracy of the members of the research sample. Finally they recommended the need to focus on physical exercise using the special tools for different categories in the game of the Boccia for members of the research sample.